Reperfused human umbilical cords as an ex vivo model for ECMO cannulation in artificial placenta technology - Hoyos Banchon, Camila; Heyer, Jan; van Haren, Juliette S.; Orlikowsky, Thorsten; Steinseifer, Ulrich; Jansen, Sebastian V.; Schoberer, Mark (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundEstablishing an extracorporeal circuit for artificial placenta technologies requires the cannulation of the umbilical vessels with large-bore cannulas. So far, this procedure could only be performed in large-animal models. We present the methodology and a novel test setup for reperfusion of human umbilical cords to develop and train cannulation procedures.Methods67 umbilical cords and placentas were harvested during cesarian sections, 15 cm umbilical cord specimen and fetal blood were used for these experiments. All three umbilical vessels were flushed, terminal cannulated, and connected to a circuit. We performed systematic validation tests on reperfusion of 15 umbilical cord specimens, followed by an ECMO cannulation of all three reperfused vessels.ResultsThe terminal cannulation succeeded in 43 of 67 cases. 15 of these were included in the validation study. A physiological flow of 71.2 mL/min ±3.9 mL/min (mean ± SD) could be established. ECMO Cannulation of at least one artery and one vein succeeded in 9 of 15 cases, and cannulation of all three vessels in five cases.ConclusionReperfusion of human umbilical cord specimens with fetal blood can provide a biosimilar model for the development, testing, and training of umbilical vessel cannulation with large-bore cannulas.